Thermal comfort in technical school: assessment survey approach - Makhtar, Nor Kamilah; Ismail, Ahmad Rasdan; Jusoh, N. (Faculty of Mechanical Engineering, Universiti Malaysia Pahang, 2010)
A field study on the students’ performance in the thermal comfort for acceptability environment assessment was carried out in one of technical school in Selangor, located in the west region of Malaysia. The buildings were mechanically ventilated by fans. The study was made on 4 different days from morning until noon. All the windows were left open for natural ventilation. A subjective measurement was conducted using survey questionnaire. The Predicted Mean Vote (PMV) was calculated using ASHRAE Thermal sensation scale which has been proposed earlier by Fanger in 1970 for the measured data. Further Predicted Percentage Dissatisfied (PPD) was used to estimate the thermal comfort satisfaction of the occupant. The study reveals that 70% of the students’ population at the classroom is likely to be dissatisfied with the thermal comfort. The empirical finding is also closely related to the perception study by survey questionnaire distribution. Some improvement on the design of the school’s uniform that being used by the students must be made and provides a classroom with better ventilation in order to increase the thermal comfort among the students.